Load Impact Analysis Towards Power Loss in Distribution Substation in Wlingi District - Setyawan, Tony Agus; rahmawati, yuni (Frontier Energy System and Power Engineering, 2019)
This research aimed to find: (1) the distribution substations configuration in Kesamben Feeder, Wlingi District, (2) how much was the loading in those distribution substations, (3) how much load imbalance in the distribution substation’s load, and (4) how much was the power loss towards the imbalance load. This research used descriptive analysis by analyzing the loading imbalance towards the power loss of distribution substation in one feeder. The results showed that the higher percentage of loading imbalance meant higher power loss. However, although an imbalance percentage was more significant than a smaller percentage, the power loss that occurred might be more substantial due to the probable higher loading percentage so that the power loss in the substation was also influenced by the loading value, apart from the load imbalance.